Pelatihan Pembuatan Lilin Hias Untuk Meminimalisir Limbah Minyak Jelantah Bagi Masyarakat Desa Labuhan Sumbawa - Nurlaila Agustikawati; Desy Fadilah Adina Putri; Fitri Setianingsih (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
The high consumption of cooking oil can result in the use of cooking oil being carried out repeatedly even though the use of cooking oil can only be used within certain limits. Used cooking oil has not been widely used by the community in several areas, including the community in Labuhan Village, Sumbawa. The community in Labuhan Village, Sumbawa, has many MSMEs related to cooking oil, including sellers of fried foods, crackers, skin crackers and food stalls, who need to use used cooking oil to minimize used cooking oil waste and increase their income from managing used cooking oil. So the aim of this service activity is to provide knowledge and improve skills as well as encourage the commitment of the Labuhan Sumbawa Village community in managing used cooking oil waste. This form of community service program takes the form of improving skills in the community through training activities. This community service activity is an expert activity with the stages of counseling, demonstration and training. The result of this service activity is an increase in participants' knowledge and skills in managing used cooking oil waste and there is a commitment to managing used cooking oil waste in protecting the environment and family health.